Search for new non-resonant phenomena in high-mass dilepton final states with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Klassen, Martin; et al. (Journal of high energy physics, 2020)
A search for new physics with non-resonant signals in dielectron and dimuon final states in the mass range above 2 TeV is presented. This is the first search for non-resonant signals in dilepton final states at the LHC to use a background estimate from the data. The data, corresponding to an integrated luminosity of 139 fb−1, were recorded by the ATLAS experiment in proton-proton collisions at a center-of-mass energy of $$ \sqrt{s} $$= 13 TeV during Run 2 of the Large Hadron Collider. The benchmark signal signature is a two-quark and two-lepton contact interaction, which would enhance the dilepton event rate at the TeV mass scale. To model the contribution from background processes a functional form is fit to the dilepton invariant-mass spectra in data in a mass region below the region of interest. It is then extrapolated to a high-mass signal region to obtain the expected background there. No significant deviation from the expected background is observed in the data. Upper limits at 95% CL on the number of events and the visible cross-section times branching fraction for processes involving new physics are provided. Observed (expected) 95% CL lower limits on the contact interaction energy scale reach 35.8 (37.6) TeV.
The Atlas collaboration: G. Aad, V. Andrei, F. Bartels, A.E. Bolz, M. Czurylo, S. Dittmeier, M. Dunford, D.E. Ferreira de Lima, S. Franchino, L. Helary, J. Jongmanns, M. Klassen, A. Krishnan, M. Mkrtchyan, F. Napolitano, P. Ott, A. Schoening, H.-C. Schultz-Coulon, T. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, S. Weber, M. Wessels, X. Yue [und 2916 weitere]
Gesehen am 15.04.2021